Sacubitril/Valsartan vs ACE Inhibitors or ARBs - Endurance Evbayekha, MD; Abiodun Benjamin Idowu, MD; Shane LaRue, MD (JACC: Advances, 2025)
Background: Sacubitril/valsartan (SAV) is crucial for managing heart failure (HF). Randomized clinical trials have shown SAV's superiority over angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARBs) in reducing N-terminal pro-B-type natriuretic peptide levels. However, results for cardiovascular (CV) mortality, HF rehospitalization, and all-cause mortality have been mixed. Objectives: This study aimed to determine hard endpoints among the population with HF treated with SAV vs ACEI/ARBs and conduct a comprehensive risk-benefit analysis of the safety profile for SAV vs ACEI/ARB. Methods: We queried PubMed, EMBASE, Scopus, and the Cochrane Central Register of Controlled Trials for randomized clinical trials from inception to November 2023. We included studies that compared SAV to ACEI or ARBs and reported hard endpoints, including all-cause mortality, CV mortality, and HF rehospitalizations. Random effect model was used, and categorical values were analyzed using risk ratios (RRs) and 95% CI. The I2 test was used to assess between-study heterogeneity. Publication bias was assessed via funnel plots and the Egger test. This study was registered in PROSPERO (CRD42024497661). Results: The study included a total of 14 trials (n = 25,167). SAV reduced all-cause mortality in the population with an ejection fraction (EF) ≤40% (RR: 0.88; 95% CI: 0.81-0.94; P = 0.0006), but not in those with EF >40% (RR: 0.97; 95% 0.85-1.11; P = 0.67). There was no difference in CV mortality across EF spectrums (RR: 0.9; 95% CI: 0.79-1.03; P = 0.13). HF readmission was lower in the SAV-treated group regardless of EF (RR: 0.85; 95% CI: 0.79-0.91; P = 0.00001). Conclusions: The SAV-treated group, across all EF spectrum, was less likely to be rehospitalized than the ACEI/ARB-treated group. However, all-cause mortality reduction was only noted in the SAV group with EF <40%. No reduction in CV-related mortality was observed across the EF spectrum.